Deformation analysis of deep foundation pit in soft soil area considering space–time effect - Lide Shi; Wanrong Yu; Lei Fu (The Journal of Engineering, 2019)
Taking the deep foundation pit project of Taojiazhai in Shanghai as the background, combined with the real-time monitoring data, the data variation law of several monitoring items during the excavation of foundation pit are analysed. The results show that the axial force of the support, the lateral displacement of the retaining structure and the uplift of the column increase greatly during the excavation of the foundation pit, and tend to be stable after the floor starts to work. The maximum lateral displacement and the depth of the maximum lateral displacement of the maintenance structure increase with the increase of the excavation depth, and the extremum has a definite relationship with the excavation depth. The lateral displacement of maintenance structure and adjacent pipelines are small at the corner of foundation pit and large at the centre of pit wall. Ground settlement around the foundation pit increases first and then decreases along the direction away from the wall. The calculation formula of the settlement of the soil can be revised by introducing the stiffness correction function to predict the settlement of the pipeline.